Challenges to Pharmacy Education In Asian Region (Part 1) - Hassaan A. Rathore; Lee Shi Wei (Archives of Global Professionals, 2010)
"Professionalism" in pharmacy profession is endeavored and aimed at by almost all the pharmacy education institutions. Indeed it is one of the core objectives aimed in developing pharmacy curricula. However to this broad terminology there is no clear consensus on definition of professionalism found in literature and thus becomes a big challenge for academicians involved in curriculum development. Ironically, professionalism is not the only challenge which pharmacy educationists have to cope with.There are several other fronts faced by pharmacy education in this era of rapid progress.